Uniform estimates for local properties of analytic functions in a complete Reinhardt domain - A. I. Bandura; T.M. Salo (Математичні Студії, 2024)
Using recent estimates of maximum modulus for partial derivatives of the analytic functions with bounded $L$-index in joint variables we describe maximum modulus of these functions at the polydisc skeleton with given radii by the maximum modulus with lesser radii. Such a description is sufficient and necessary condition of boundedness of $L$-index in joint variables for functions which are analytic in a complete Reinhardt domain. The vector-valued function $L$ is a positive and continuous function in the domain and its values at a point is greater than reciprocal of distance from the point to the boundary of the Reinhardt domain multiplied by some constant.